A Randomized Phase 2 Study of Erenumab for the Prevention of Episodic Migraine in Japanese Adults. Issue 10 (14th October 2019) - Sakai, Fumihiko; Takeshima, Takao; Tatsuoka, Yoshihisa; Hirata, Koichi; Lenz, Robert; Wang, Yi; Cheng, Sunfa; Hirama, Toshiyasu; Mikol, Daniel D.
Abstract : Objective: A phase 2, double‐blind, placebo‐controlled study to evaluate the efficacy and safety of erenumab for the prevention of episodic migraine in Japanese patients was conducted. Background: Previous global clinical studies have demonstrated the efficacy of erenumab in the prevention of migraine. Methods: Patients were randomized to placebo or erenumab 28, 70, or 140 mg administered subcutaneously once per month for 6 months. The primary endpoint was change from baseline in mean monthly migraine days over months 4‐6 of the double‐blind treatment phase. Secondary endpoints included the proportion of patients achieving ≥50% reduction from baseline in mean monthly migraine days (≥50% response) and change from baseline in mean monthly acute migraine‐specific medication treatment days (MSMD) and mean Headache Impact Test (HIT‐6™) scores. Efficacy outcomes were also determined at months 1, 2, and 3. Results: Four hundred and seventy five patients were randomized 2:1:2:2 to placebo and erenumab 28, 70, and 140 mg, respectively. Greater reductions in monthly migraine days were observed for erenumab vs placebo with differences of –1.25 (95% CI: –2.10 to –0.41; P = .004), –2.31 (95% CI: –3.00 to –1.62; P < .001), and –1.89 (95% CI: –2.58 to –1.20; P < .001) days for erenumab 28, 70, and 140 mg. The odds of having a ≥50% response were 3.2, 5.6, and 4.7 times greater for erenumab 28 mg (95% CI: 1.30‐7.88; P = .009), 70 mg (95% CI: 2.60‐12.06; P < .001), and 140 mg (95% CI: 2.24‐9.99; P < .001) than for placebo. Greater reductions from baseline in mean acute monthly MSMD were observed for erenumab vs placebo with differences of –1.07 (95% CI: –1.80 to –0.35; P = .004), –2.07 (95% CI: –2.66 to –1.49; P < .001), and –2.04 (95% CI: –2.63 to –1.45; P < .001) days for erenumab 28, 70, and 140 mg. Erenumab 70 and 140 mg also resulted in greater improvements in HIT‐6™ scores. The safety profile was similar across treatment groups. The most common adverse event was nasopharyngitis, which occurred in 29.4% of patients in the placebo group and 28.9%‐33.3% of patients in the erenumab groups. Conclusion: Monthly subcutaneous injections of erenumab 70 mg demonstrated statistically significant and numerically maximal efficacy with a favorable safety profile, suggesting that erenumab is a potential new therapy for migraine prevention in Japan.